Transformasi Pengucapan Syukur: Identitas dan Relasi Sosial Era Pandemi Covid-19 di Tomohon - Weol, Wolter; Heydemans, Nency Aprilia; Langi, Fienny Maria (Institut Agama Kristen Negeri Manado, 2021)
This paper describes the transformation of gratitude: identity and social relations during the Covid-19 pandemic era in Tomohon. The expression of gratitude to God Almighty (Opo Empung Wailan Wangko) was inherited from the ancestors of the Tou (people) of Minahasa for the yields obtained in the form of offerings. This one gratitude is done every one person in social relations and cultural integration. This article aims to analyze the transformation of gratitude carried out in Tomohon during the Covid-19 Pandemic era. This study reveals the social identity theory from the sociological paradigm by Steph Lawler (2014) which functions as a relationship between relatives as individuals, which in this study is called family, basudara. The article data uses field research with the method of observation and in-depth interviews. The results of the research are expected to help the government and society in preventing Covid-19 so as to minimize consumptive lifestyles and maintain distance. There are three values ​​that are useful for building life, namely the value of brotherhood, mutual cooperation (mapalus) and spirituality.